QoS-RRC: Integrated QoS routing and resource provisioning mechanism for future internet - Figueiredo, Sergio Miguel Calafate de (2012)
Generic Path (GP) is a new connectivity paradigm proposed to facilitate the inclusion of new applications and services abstracting communications between entities, regardless of their location or architectural layer. This paper enhances the GP architecture with a new mechanism integrating QoS-Routing and Resource Control (QoS-RRC) strategies to dynamically control GP session requirements regarding QoS and connectivity. This solution uses over-provisioning and admission control, and is aimed at multi-party time-sensitive sessions. Initial performance evaluation was carried out in Network Simulator v.2 (NS-2), showing capabilities in reducing overall signaling load in comparison with a value-added per-flow approach.